Pyrrolizidine alkaloids in members of the Boraginaceae from Sinai (Egypt) - El-Shazly, Assem; El-Domiaty, Maher; Witte, Ludger; Wink, Michael (Biochemical systematics and ecology, 1998)
Altogether 40 pyrrolizidine alkaloids were detected in the alkaloid extracts of Paracaryum rugulosum, P. intermedium, Anchusa milleri, Gastrocotyle hispida (syn. Anchusa hispida), Anchusa arvensis, Lappula spinocarpos, Trichodesma africanum, Alkanna orientalis, and Alkanna tuberculata (syn. A. tinctoria) which were analyzed by capillary GLC and GLC-MS. 24 alkaloids were unambiguously identified by comparing their specific retention indices and mass fragmentations with those of authentic alkaloids and literature data. The relevance of PAs as chemical defence compounds for desert plants against herbivores is discussed.